Foreword No 2/2021 - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2021)
Globally, in June 2021, the World Bank improved its growth forecast for 2021 by 1.5 percentage points, to 5.6%, which means that the world economy will record the strongest growth in the last 80 years. However, the international financial institution warns that many countries, especially the poor ones, are left behind and will need several years to return to pre-pandemic levels.